The impact of IT capabilities and supply chain integration capabilities on concurrent engineering success - LIU, YING (2019)
Although many Chinese manufacturing enterprises have abundant resources, they are not as good as the world's leading enterprises in new product development (NPD). The main reason is that these Chinese enterprises do not apply their resources to action. Currently, the manufacturing industry usually uses concurrent engineering (CE) to develop new products. To improve the success rate of concurrent engineering and thus improve business performance, companies need to make full use of information technology (IT) capabilities and supply chain integration (SCI) capabilities. Based on resource-action-performance (RAP) theory and organizational information processing theory (OIPT), this research studies the influence of IT capabilities (IT management, IT infrastructure, business IT strategic thinking) and supply chain integration capabilities (supplier integration, customer integration and internal integration) on the implementation of concurrent engineering by adopting the method of structural equation model. The result shows that business IT strategic thinking, internal integration, and IT infrastructure have positive effects on concurrent engineering while customer integration, IT management and supplier integration have no positive influence on concurrent engineering. Also, concurrent engineering has a positive impact on business performance. Therefore, Chinese manufacturing enterprises should actively implement concurrent engineering. Furthermore, these enterprises should give full attention to business IT strategic thinking, IT infrastructure, and internal integration when performing concurrent engineering.